Immunoporosis: Immunology of Osteoporosis—Role of T Cells - Srivastava, Rupesh K.; Dar, Hamid Y.; Mishra, Pradyumna K. (Frontiers in Immunology, 2018)
The role of immune system in various bone pathologies such as osteoporosis, osteoarthritis and rheumatoid arthritis is now well established. This had led to the emergence of a modern field of systems biology called as osteoimmunology, an integrated research between fields of immunology and bone biology under one umbrella. Osteoporosis is one of the most common inflammatory bone-loss conditions with more than 200 million individuals affected worldwide. T helper cells along with various other immune cells are major players involved in bone homeostasis. In the present review, we specifically discuss the role of various defined T lymphocyte subsets (Th cells comprising Th1, Th2, Th9, Th17, Th22, regulatory T cells, follicular helper T cells, natural killer T cells, γδ T cells and CD8+ T cells) in the pathophysiology of osteoporosis. The study of the specific role of immune system in osteoporosis has now been proposed by our group as “Immunoporosis: The immunology of osteoporosis” with special emphasis on the role of various subsets of T lymphocytes. The establishment of this new field had been the need of the hour due to the emergence of novel roles of various T cell lymphocytes in accelerated bone loss observed during osteoporosis. Activated T cells either directly or indirectly through the secretion of various cytokines and factors modulate bone health and thereby regulate bone remodelling. Various studies have summarized the role of inflammation in pathogenesis of osteoporosis, but very few reports had delineated the precise role of various T cell subsets in the pathobiology of osteoporosis. The present review thus for the first time clearly highlights and summarizes the role of various T lymphocytes in the development and pathophysiology of osteoporosis, giving birth to a new field of biology termed as “Immunoporosis”. This novel field will thus provide an overview of the nexus between the cellular components of both bone and immune systems, responsible for the observed bone loss in osteoporosis. A molecular insight into the upcoming and novel field of immunoporosis would thus lead to development of innovative approaches for the prevention and treatment of osteoporosis.